Neotropical species of Lecaniobius Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae): key and description of two new species. - N. Myartseva, Svetlana; Ruíz-Cancino, Enrique; Coronado-Blanco, Juana María (Instituto de Ecología, A.C., 2010)
A review of neotropical species of the genus Lecaniobius is given, with a key to identify it. Lecaniobius mexicanus sp. n. from Mexico and L. nicaraguensis sp. n. from Nicaragua are described; L. capitatus Gahan and L. cockerellii Ashmead are redescribed, including some additional morphological characteristics.